Behavioural Pattern as Indicator of Different Stages of Estrus in Sahiwal Cows (Indian Journal of Animal Production and Management, 2024)
The reproductive efficiency of dairy animals  is having a direct impact on productivity and  profitability of dairy farms. Therefore, reproduction  management is a major concern in dairy industry.  Communication of the timing of physiological event  of ovulation and coordination of sexual behavior are  important for successful fertilization. The success  rate of artificial insemination in cattle mainly  depends on the time of estrus it is inseminated.  Inefficient and inaccurate heat detection results in  failure of conception during that attempt, which in  turn leads to significant economic losses. The  efficient and accurate detection of estrus and the  timing of AI has remained major challenge to  improve reproductive and economic efficiencies of  dairy farms. To have a simple and accurate  technique for optimizing the time of insemination,  present investigation was performed on healthy,  cyclic Sahiwal cows which had calved recently and  were maintained at DDD farm of LFC, DUVASU,  Mathura with an aim to investigate the behaviour of  the cows in order to discriminate the various stages  of estrus. The behavioral attributes of teaser bull  and experimental cows were observed during three  different stages i.e. onset of estrus, standing heat  and non-estrus stages of same cows. It was  observed that frequency of mounting by teaser  bulls, frequency of Flehmen reaction by teaser  bulls, restlessness of Sahiwal cows, bellowing and  frequency of urination were all significantly affected  by different stages of estrus i.e onset of estrus,  standing heat and non-estrus.
Keywords: behavioural pattern; estrus stage; Sahiwal cows